2013
DOI: 10.1093/nar/gkt369
|View full text |Cite
|
Sign up to set email alerts
|

The hnRNP F/H homologue of Trypanosoma brucei is differentially expressed in the two life cycle stages of the parasite and regulates splicing and mRNA stability

Abstract: Trypanosomes are protozoan parasites that cycle between a mammalian host (bloodstream form) and an insect host, the Tsetse fly (procyclic stage). In trypanosomes, all mRNAs are trans-spliced as part of their maturation. Genome-wide analysis of trans-splicing indicates the existence of alternative trans-splicing, but little is known regarding RNA-binding proteins that participate in such regulation. In this study, we performed functional analysis of the Trypanosoma brucei heterogeneous nuclear ribonucleoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 80 publications
0
49
0
Order By: Relevance
“…In addition, the protein recognition site, AAGAA, is located around the 3′ splice site and the poly (A) site. 60 In this study, we found that substrates downregulated by TSR1 and TSR1IP silencing contain weaker splicing signals such as shorter and pyrimidinepoor PPTs, and that the regulated genes have more heterogeneous poly (A) site selection. RNA-seq of these transcriptomes may reveal additional substrates, especially non-abundant transcripts that are not detected by the microarray analysis but also have weak splicing signals, and hence, rely on SR proteins for their splicing.…”
Section: Factors Involved In Splicing Regulation In Metazoa and The Rmentioning
confidence: 67%
“…In addition, the protein recognition site, AAGAA, is located around the 3′ splice site and the poly (A) site. 60 In this study, we found that substrates downregulated by TSR1 and TSR1IP silencing contain weaker splicing signals such as shorter and pyrimidinepoor PPTs, and that the regulated genes have more heterogeneous poly (A) site selection. RNA-seq of these transcriptomes may reveal additional substrates, especially non-abundant transcripts that are not detected by the microarray analysis but also have weak splicing signals, and hence, rely on SR proteins for their splicing.…”
Section: Factors Involved In Splicing Regulation In Metazoa and The Rmentioning
confidence: 67%
“…Our data provide further evidence supporting the important role of post‐transcriptional gene‐expression regulators in controlling T. brucei development. Among factors with previously demonstrated regulatory activity are the RNA‐binding proteins RBP10 and hnRNP F/H, two proteins with clear functions in establishing a bloodstream‐form type transcriptome (Wurst et al ., ; Gupta et al ., ; De Pablos et al ., ), which are highly up‐regulated in metacyclic trypanosomes (Fig. A).…”
Section: Discussionmentioning
confidence: 99%
“…Among factors with previously demonstrated regulatory activity are the RNA-binding proteins RBP10 and hnRNP F/H, two proteins with clear functions in establishing a bloodstream-form type transcriptome (Wurst et al, 2012;Gupta et al, 2013;De Pablos et al, 2017), which are highly up-regulated in metacyclic trypanosomes (Fig. 5A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two life cycle stages are routinely cultured in the laboratory: the bloodstream form, which is similar to the forms that multiply in mammalian blood and tissue fluids, and the procyclic form, which is similar to the parasites in the tsetse fly midgut. Different mRNA levels-and also regulation during differentiation-are achieved by modulation of mRNA decay (17) and trans-splicing (18)(19)(20). Trypanosome mRNA decay pathways are similar to those of other eukaryotes: mRNAs are deadenylated by a CAF1-NOT complex (21), then the mRNA body is attacked from the 3= end by the exosome (22)(23)(24) and in the 5=-3= direction by XRNA (25).…”
mentioning
confidence: 99%